Investor and Industry Perspectives on Investment Advisers and Broker-Dealers - Hung, Angela A. (RAND Corporation, 2008)
In theory, financial professionals are relatively distinct: A broker-dealer conducts transactions in securities on behalf of itself and others; and an investment adviser provides advice to others regarding securities. Different laws regulate each type of professional, but boundaries have blurred. This report examines current business practices and investor understanding of each type.